Perceived Usefulness and Ease Influence Outpatient Inten-tion to Use Electronic Medical Records Through User Atti-tudes - Suwanda Hendrawan; Duta Liana; Munawar Munawar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examined the influence of perceived usefulness and perceived ease of use on the intention to use electronic medical records (EMRs) with attitude as an intervening variable at Cenka Hospital. Differences in staff perceptions regarding the benefits and convenience of EMR implementation were identified as factors contributing to the low intention to use the system. Some healthcare workers perceived limited benefits from EMRs, reducing their motivation to utilize the technology effectively. The study aimed to identify strategic factors that could improve EMR adoption, particularly attitudes, perceived usefulness, and perceived ease of use.A quantitative causal research design was employed using descriptive analysis and the three-box method. The respondents consisted of 70 hospital staff members selected through a saturated sampling (census) technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).The findings revealed that perceived usefulness, perceived ease of use, and attitude each had a significant positive effect on the intention to use EMRs. In addition, perceived usefulness and perceived ease of use positively influenced users’ attitudes toward EMR implementation. However, attitude did not mediate the relationship between perceived usefulness and intention to use EMRs, nor the relationship between perceived ease of use and intention.The study recommends improving staff competence through continuous training, strengthening information technology support teams, regularly updating EMR systems, and enhancing infrastructure such as internet speed and computer specifications to optimize EMR utilization and reduce patient care errors.